2021
DOI: 10.1001/jamanetworkopen.2021.40674
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Nativity With Race and Ethnicity in Preeclampsia—Broadening the Assessment of Social Determinants of Maternal Health

Abstract: There are approximately 4 million births annually in the US, and approximately 1 in 5 of these births are complicated by 1 or more interrelated adverse pregnancy outcomes (APOs), including preeclampsia, preterm delivery, and birth of an infant who is small for their gestational age. 1 APOs are increasing in incidence, have shared upstream risk factors, and have important health implications for both the birthing person and offspring. Numerous studies have demonstrated the associations between APOs and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Given the disparities in maternal health, there is a need for greater advocacy at institutional, state, national, and international levels to improve cardiovascular care of women during and after pregnancy. 18 19 21 22 30 This includes forming and participating in institutional and state/federal maternal mortality and morbidity review committees and engagement in national and international professional and foundational societies. Formal training in cardio-obstetrics provides education across disciplines and a fresh perspective on the heterogeneous and complex care required for optimal outcomes.…”
Section: Career Opportunitiesmentioning
confidence: 99%
“…Given the disparities in maternal health, there is a need for greater advocacy at institutional, state, national, and international levels to improve cardiovascular care of women during and after pregnancy. 18 19 21 22 30 This includes forming and participating in institutional and state/federal maternal mortality and morbidity review committees and engagement in national and international professional and foundational societies. Formal training in cardio-obstetrics provides education across disciplines and a fresh perspective on the heterogeneous and complex care required for optimal outcomes.…”
Section: Career Opportunitiesmentioning
confidence: 99%
“…While research reveals the major medical causes of maternal mortality (Collier and Molina 2019), more recent studies examined social determinants of (i.e. environmental, social, and economic conditions that surround) poor maternal health outcomes (Crear-Perry et al 2021; Gadson, Eloho, and Mehta 2017; Shah, Kershaw, and Khan 2021). A recent review of literature on the social determinants of maternal mortality offered strong evidence of the role of race and ethnicity, insurance, and education in maternal deaths, but noted “a lack of diversity in the social determinants of health and maternal outcomes literature, including the type of determinants studied, type of study design, and exploration of potential mechanism that underlie the observed association” (Wang et al 2020:911).…”
Section: Introductionmentioning
confidence: 99%